Islam Dan Budaya Minangkabau Dalam Film Tenggelamnya Kapal Van Der Wijck - Wibisena, Riesangaji; Iqbal, Moch (DAWUH : Islamic Communication Journal, 2021)
This research is titled "Islam and Minangkabau Culture in the Van Der Wijck Ship Sinking Film" The purpose of this study is to describe the relationship between Islam and Minangkabau culture in the Van Der Wijck Ship Sinking film, and to describe the propaganda messages for the Van Der Wijck Sinking film. This research uses a qualitative method by using descriptive method in which the researcher tries to describe how the Relationship between Islam and Minangkabau culture in the movie Van Der Wijck Sinking. The object of this research is the Van Der Wijck Ship Sinking. This study uses the theory of Charles Sanders Pierce Charles Sanders emphasizes the importance of meaning for humans by saying the main references of humans in using Pierce's ratio divide it into 3 namely: Icons, Indexes, and Symbols. The results of this study determine the relationship between Islam and Minangkabau culture symbolized in the sinking film Van Der Wijck Ship created through the use of language, clothing, and customs, which uses which films, films, films, what could be used by the Minangkabau people in 1930- n, a map often used in daily life, a picture of the young batipuh who are fervently listening and studying religion.